Determination of blood loss in bimaxillary surgery: does the formula and the time point affect results?. Issue 4 (April 2022) - Schwaiger, M.; Edmondson, S.-J.; Merkl, M.; Gary, T.; Zemann, W.; Wallner, J.
Abstract: The amount of blood loss determined in orthognathic surgery differs greatly among studies. This can be attributed to the inhomogeneity in study cohorts analysed, but may also be a result of the varying methodologies used for blood loss determination. However, this has yet to be explored. Thus, the aim of this study was to investigate the extent to which the formula and time point used to measure blood loss affect the blood loss volume, determined in a homogeneous cohort undergoing bimaxillary surgery. Blood loss was calculated at 24 and 48 hours postoperatively using the haemoglobin balance method and the formula of Hurle et al. The estimated total blood volume was established based on the formulae of Nadler et al. and Choi et al. Differences in blood loss volume with respect to time point and formula were analysed and compared. Fifty-four patients were included in the final analysis. Statistically significant differences in blood loss were observed: a significant increase in the blood loss volume from 24 hours to 48 hours postoperatively was detected. When comparing the formulae used, blood loss differed significantly at 24 hours after surgery; however no such difference resulted at 48 hours postoperatively. These findings imply that the time point of measuring blood loss is highly relevant, whereas the formulae applied seem to have less of an impact on the blood loss volumes calculated.